2014
DOI: 10.3906/biy-1307-52
|View full text |Cite
|
Sign up to set email alerts
|

In vitro micropropagation from immature embryos of the endemic and endangered Muscari muscarimi Medik.

Abstract: An efficient in vitro bulblet production procedure from immature zygotic embryos of endemic and endangered Muscari muscarimi Medik. was described in the current study. Zygotic embryos were first isolated from immature seeds and cultured on different nutrient media compositions supplemented with various combinations of α-naphthalene acetic acid (NAA), picloram, dicamba, 6-benzylaminopurine (BAP), and thidiazuron (TDZ). The best bulblet regeneration (59 bulblets per explant) was achieved in Murashige and Skoog (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The results of the study suggest that the indvidual regeneration on TDZ-NAA-containing MS medium was strongly influenced by the concentrations and combinations of plant growth regulators. The results are in agreement with Uranbey (2010 a, b), Uranbey et al (2011), Ozel et al (2007, 2009, 2015, Vaziri et al (2014) and Uzun et al (2014), who reported the propagation of other Turkish Muscari species using different cytokinins and auxin concentrations.…”
Section: Bulblet Regeneration Behavioursupporting
confidence: 90%
“…The results of the study suggest that the indvidual regeneration on TDZ-NAA-containing MS medium was strongly influenced by the concentrations and combinations of plant growth regulators. The results are in agreement with Uranbey (2010 a, b), Uranbey et al (2011), Ozel et al (2007, 2009, 2015, Vaziri et al (2014) and Uzun et al (2014), who reported the propagation of other Turkish Muscari species using different cytokinins and auxin concentrations.…”
Section: Bulblet Regeneration Behavioursupporting
confidence: 90%
“…Contrarily, Petric et al (2011) revealed the importance of a low TDZ concentration of 0.05-0.50 mg/L for optimum bulblet formation for F. melegris. However, negative effects of a higher TDZ concentration (2.0 mg/L) on bulblet formation and bulblet numbers of M. muscarimi Medic (Uzun et al, 2014b) have also been reported. In vitro regenerated bulblets from germination or regeneration experiments failed to acclimatize in pots containing peat moss, perlite, or vermiculite alone or in different combinations (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are some reports concerning somatic embryogenesis in bulb explants of M. neglectum inoculated with various concentrations of BA alone or in combination with NAA (Karamian et al, 2010) and encapsulation of somatic embryos obtained from protoplast cultures (Karamian et al, 2011). Recently, Uzun et al (2014) reported the best bulblet regeneration in M. muscarimi using MS medium containing 4.0 mg/L BA and 0.50 mg/L NAA after 1 year of culture initiation. On the other hand, there have been several reports on tissue culture studies via leaf and callus cultures derived from flower buds (Suzuki and Nakano, 2001;Mori and Nakano, 2004;Azad and Amin, 2012), protoplast cultures of the Muscari cultivar Blue Pearls (Nakano et al, 2005), and Agrobacterium-mediated production of transgenic M. armeniacum (Suzuki and Nakano, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture applications might be appropriate for the bulblet production in vitro and might also be assessed as a prevailing instrument for ex situ conservation of geophytes against their intensive collection from natural habitats. However, micropropagation of several Muscari species, such as M. racemosum (Kromer, 1989), M. macrocarpum Sweet (Ozel et al, 2007), M. aucheri (Uranbey, 2010a), M. azureum (Uranbey, 2010b), M. mirium (Nasırcılar et al, 2011), and M. muscarimi (Uzun et al 2014), has been established. There are also some reports concerning plantlet regeneration of M. armeniacum via callus cultures (Suzuki and Nakano, 2001;Mori and Nakano, 2004;Azad and Amin, 2012) and protoplast cultures (Nakano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation